PFMG1 promotes osteoblast differentiation and prevents osteoporotic bone loss. Issue 2 (4th January 2018) - Li, Liyuan; Wang, Pan; Hu, Kaiqiang; Wang, Xiaoyan; Cai, Wenping; Ai, Chao; Liu, Shangfeng; Wang, Zhao
Abstract : Nacre is a widely used mineral medicine that has been reported to have beneficial effects in bone remodeling without an increase in inflammation. Water‐soluble nacre matrix has been demonstrated to be responsible for the effect, yet core active ingredients are unknown. Pinctada fucata mantle gene 1 (PFMG1) was first discovered in the mantle tissue of Pinctada fucata. The protein has 2 EF‐hands, a calcium‐binding domain. PFMG1 protein can affect the growth of calcium carbonate crystals in vitro. Here, we demonstrate that PFMG1 affects cell‐cycle distribution and promotes preosteoblast proliferation. PFMG1 accelerates preosteoblast differentiation and extracellular matrix mineralization. During the differentiation process, PFMG1 increases the expression level of osteoblastic marker genes and activates the Erk signaling pathway. PFMG1 also accelerates calcium crystal aggregation in culture medium and suppresses osteoclast formation. Moreover, PFMG1 prevents bone loss caused by ovariectomy. RNA sequencing analysis demonstrated that PFMG1 stimulates genes that are associated with tissue development and ossification, which indicated new genes that function in bone remodeling. Our findings demonstrate the therapeutic potential of PFMG1 from nacre as a novel medicine for osteoporosis.—Li, L., Wang, P., Hu, K., Wang, X., Cai, W., Ai, C., Liu, S., Wang, Z. PFMG1 promotes osteoblast differentiation and prevents osteoporotic bone loss. FASEB J. 32, 838–849 (2018). www.fasebj.org